A new species of the electric fish Microsternarchus Fernández-Yépez 1968 (Gymnotiformes: Hypopomidae) from the lower Amazon basin, Brazil - Sousa, Trycia; Wosiacki, Wolmar B.; Muriel-Cunha, Janice; Prudente, Bruno S.; Sousa, Rodrigo S.; Peixoto, Luiz A. W. (Zootaxa, 2024)
A new species of Microsternarchus is described from clear water streams in the lower Rio Amazonas basin, Brazil, increasing the known species in the genus to three. The new species is distinguished from congeners by a unique set of characters including an elongated caudal filament (35.1–36.8% of the total length) and distinct irregular suborbital blotches. A dichotomous key to the species of Microsternarchus is provided.